1968: Towards a General Secularism. (8th December 2021) - During, Simon
Abstract : The numerous interpretations and evaluations of 1968 that have been developed over the past half-century can arguably be divided into two. On one side, there are those accounts that regard 1968 as the threshold across which an older form of modernity passed to become what student revolutionaries of the period began to call late capitalism; and although late capitalism itself quickly became a fissured thing, this view has become orthodox. On the other side, there are those who insist that '68 was a Badiousian event, an outbreak of liberatory possibilities to which we not only have a responsibility to remain faithful, but which provided a template for later more or less insurrectionary movements; undoubtedly the strongest argument for '68's enduring radical meaning and potential has been made by Kristin Ross in her 2002 book, May '68 and its Afterlives . This article is partly committed to arguing for a middle way between these two views. I accept that the processes leading to and following the events of 1968 triggered the development of a new kind of capitalist society as well as formed the template for the radicalisms we now have. This mediation might seem to involve a contradiction, but in the end it is more accurate not to see these two views as they see themselves, namely as enemies, but rather as dialectically and functionally united. Without the kind of capitalism that the 1960s triggered, no radical movement politics; without radical, post-communist movement politics, no such late capitalism. To see that, we need to think about '68 in larger contexts and terms than is usual. I will call the context I wish to bring to bear general secularization .